Multigram Synthesis of a Chiral Substituted Indoline Via Copper-Catalyzed Alkene Aminooxygenation - Sequeira, Fatima C. (2012)
(S)-5-Fluoro-2-(2,2,6,6-tetramethylpiperidin-1-yloxymethyl)-1-tosylindoline, a 2-methyleneoxy-substituted chiral indoline, was synthesized on multigram scale using an efficient copper-catalyzed enantioselective intramolecular alkene aminooxygenation. The synthesis is accomplished in four steps and the indoline is obtained in 89% ee (>98% after one recrystallization). Other highlights include efficient gram-scale synthesis of the (4R,5S)-di-Ph-box ligand and efficient separation of a monoallylaniline from its bis(allyl)aniline by-product by distillation under reduced pressure.